Simulation of Hybrid Filter Model to Enhanced the Quality of Noisy Images - Rathore, Vivek Singh; Kharsan, Vinod Singh (International Journal of Computer Sciences and Engineering, 2025)
The objective of this paper, provide the simulation steps of hybrid filter model that consists image denoising and image enhancement implementation over three different noises such as Salt and Pepper (SPN), Gaussian noise, Speckle (SPKN) with different noise variance in range .02 to .14. Hybrid filter works on spatial filtering techniques such as median filter and high pass filter that is operate on neighbourhood pixels. Median filter technique is used for smoothness and other(High pass) for sharpening of images and extracting the useful information in analysis process for image processing because of the input images are not always in good quality. The same concept is applied to the different images and they are compared with one another. The performance measurement is proposed with the help of Mean Square Errors (MSE), Peak-Signal to Noise Ratio (PSNR) and Signal to Noise (SNR) .So as to choose the appropriate noise for different filtering methods for any image. Result has simulated on MATLAB R2007b.